PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF SPORTSMAN - Зайцева, Юлія; Момот, Олена; Новік, Сергій (SWorldJournal, 2023)
In this article it was done, the theoretical analysis of the psychological component of the sportsman's personality; it was found that it is necessary to control the level of stress using the following methods: relaxation, visualization, control over tho